Factors causing children to drop out of school in Lalonaha Village, Wolo District, Kolaka Regency - Magdalena Limbong Lonang; Nasarudin Nasarudin; Samsi Awal (USN Kolaka, 2022)
Education is a means to improve human intelligence and skills but there are still many children who drop out of school due to various factors. The problem studied in this research is the factors that cause children to drop out of school in Lalonaha Village, Wolo District, Kolaka Regency. This research is a qualitative descriptive study. The subjects in this study were children who had dropped out of school and parents of children who had dropped out of school who lived in Lalonaha Village. The data collection techniques used in this study were interviews conducted with school dropouts and documentation. The results of this study indicate that there are 3 main factors that influence children not to continue their studies, namely: 1) social factors that are influenced by the child's association, 2) economic factors that are affected by the income of parents who cannot pay for their children's schooling, 3) accessibility of areas where influenced by distance, transportation and road facilities to school, which are the factors that cause children to drop out of school in Lalonaha Village, Wolo District, Kolaka Regency.